Increased Zinc Availability Enhances Initial Aggregation and Biofilm Formation of Streptococcus pneumoniae - Brown, Lindsey R.; Caulkins, Rachel C.; Schartel, Tyler E.; Rosch, Jason W.; Honsa, Erin S.; Schultz-Cherry, Stacey; Meliopoulos, Victoria A.; Cherry, Sean; Thornton, Justin A. (Frontiers in Cellular and Infection Microbiology, 2017)
Bacteria growing within biofilms are protected from antibiotics and the immune system. Within these structures, horizontal transfer of genes encoding virulence factors and promoting antibiotic resistance occurs, making biofilms an extremely important aspect of pneumococcal colonization and persistence. Identifying environmental cues that contribute to the formation of biofilms is critical to understanding pneumococcal colonization and infection. It has been shown that iron is essential for the formation of pneumococcal biofilms; however, the role of other physiologically important metals such as copper, zinc, and manganese has been largely neglected. In this study, we investigated the effect of metals on pneumococcal aggregation and early biofilm formation. Our results show that biofilms increase as zinc concentrations increase. The effect was found to be zinc-specific, as altering copper and manganese concentrations did not affect biofilm formation. Scanning electron microscopy analysis revealed structural differences between biofilms grown in varying concentrations of zinc. Analysis of biofilm formation in a mutant strain lacking the peroxide-generating enzyme pyruvate oxidase, SpxB, revealed that zinc does not protect against pneumococcal H2O2. Further, analysis of a mutant strain lacking the major autolysin, LytA, indicated the role of zinc as a negative regulator of LytA-dependent autolysis, which could affect biofilm formation. Additionally, analysis of cell-cell aggregation via plating and microscopy revealed that high concentrations of zinc contribute to intercellular interaction of pneumococci. The findings from this study demonstrate that metal availability contributes to the ability of pneumococci to form aggregates and subsequently, biofilms.